Crecimiento del itín (Prosopis kuntzei Harms) en la región chaqueña argentina - Ríos, Norfol Arístides; Giménez, Ana María; Moglia, Juana Graciela (Instituto de Ecología, A.C., 2016)
The growth of Prosopis kuntzei Harms (Mimosaceae) tree species of the Chaco Region of Argentina, is analyzed en this paper. Because of its technological wood properties, Prosopis kuntzei is considered an important Mimosaceae species. Mature individuals were selected from three sites of Santiago del Estero natural distribution area: Sachayoj, Brea Pozo and Suncho Corral. Dendrometric magnitudes of trees were measured diameter, shaft height and total height; 5-cm thick slices were extracted at 1meter intervals, from 0.30 cm up to the first ramification. A complete tree ring analysis, measured along four radial directions (N,E,S,W), was carried out. From stem analysis, it was observed that diameter has a growth increment of 0.6 cm per year at 59 years with a 29 cm DBH. The total height was of 7.7 m. at that age. The volume of shaft was 110.995 dm3 while form coefficient had not a defined tendency.